Savouring diversity: first steps in implementing a strategy to support community seedbanks in South Africa’s smallholder farming areas - Maluleke, Nkat Lettie; Moila, P.; Phora, G.; Dibiloane, A.; Vernooy, Ronnie; Sthapit, B.R. (Bioversity International, 2015)
This report presents the findings of a field mission to Limpopo and Eastern Cape provinces of the Republic of South Africa, following a previous mission which had recommended establishing pilot community seedbanks in each province. See previous report Embracing diversity: inputs for a strategy to support community seedbanks in South Africa’s smallholder farming areas. Report of field visits to Limpopo and Eastern Cape